Using Acoustic Emission for Measuring Surface Roughness - Rozlivka Jakub; Kašpar Václav; Dostál Petr; Černý Michal; Hajtman Benjamín; Žarnovský Jozef (Acta Technologica Agriculturae, 2020)
This paper is focused on exploring and utilizing the acoustic emission and its behaviour during surface roughness measurement. Surface quality or coating properties significantly affect the reliability and durability of operations. Three samples were selected for an experiment to demonstrate the possibility of measuring the roughness of surface textures by means of acoustic emission method (AE). These samples were made of the following materials: sample A2 – EN 54SiCr6 steel formed in water, austenitized at 850 °C for 20 minutes, sample A3 – non-heat-treated spheroidal graphite cast iron, and sample B5 – abrasion resistant austenitic manganese steel. The surfaces were subjected to the same surface treatments (roughness Ra = 1.6–3.2 μm) and measured under the same conditions. All possible measurements were measured on both x- and y-axes. Final results are presented graphically. The measured AE values showed a visible effect in the AE signals due to the lack of surface roughness.